Toponymics, etimology and documental sources: the examples of "Arosa" and "Brens" - Martínez Lema, Paulo (Madrygal. Revista de Estudios Gallegos, 2012)
The analysis and interpretation of medieval evidences of place names is essential in order to devise etymological hypothesis for their origin. This paper attempts to exemplify this methodological principle through the analysis of two Galician toponyms (Arosa and Brens) and to deal with other questions closely related to this aspect of toponymic studies.